2016
DOI: 10.1038/srep24582
|View full text |Cite
|
Sign up to set email alerts
|

The combination of three molecular markers can be a valuable predictive tool for the prognosis of hepatocellular carcinoma patients

Abstract: Based on molecular profiling, several prognostic markers for HCC are also used in clinic, but only a few genes have been identified as useful. We collected 72 post-operative liver cancer tissue samples. Genes expression were tested by RT-PCR. Multilayer perceptron and discriminant analysis were built, and their ability to predict the prognosis of HCC patients were tested. Receiver operating characteristic (ROC) analysis was performed and multivariate analysis with Cox’s Proportional Hazard Model was used for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…3). Contrasting these findings, Knaus and colleagues originally reported that expression of both DUOX1 and DUOX2 is typically suppressed in lung cancer cell lines compared to normal epithelial cells [52], and subsequent studies confirmed that DUOX1 is frequently suppressed in both lung and hepatic cancers[13, 53, 111]. Analysis of TCGA data confirms that DUOX1 is commonly suppressed in various cancers, primarily those of lung and skin, compared to adjacent healthy tissues (Fig.…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 89%
See 3 more Smart Citations
“…3). Contrasting these findings, Knaus and colleagues originally reported that expression of both DUOX1 and DUOX2 is typically suppressed in lung cancer cell lines compared to normal epithelial cells [52], and subsequent studies confirmed that DUOX1 is frequently suppressed in both lung and hepatic cancers[13, 53, 111]. Analysis of TCGA data confirms that DUOX1 is commonly suppressed in various cancers, primarily those of lung and skin, compared to adjacent healthy tissues (Fig.…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 89%
“…4). Indeed, ectopic expression of DUOX1 in liver cancers was found to correlate strongly with overall patient survival and thus was proposed as a marker for patient prognosis [53], suggests that DUOX1 silencing may be of similar importance in progression of others cancers including NSCLCs.…”
Section: Specific Roles For Duox1 and 2 In Epithelial Cancersmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocellular carcinoma (HCC) is currently ranked among the most common primary malignant cancers worldwide and is the third and fifth leading cause of death from cancer globally in men and women, respectively123. Due to lack of effective strategies for early diagnosis and pre-clinical screening for HCC in high-risk populations, the majority of patients can be treated only with loco regional therapies, resulting in limited survival benefits and tumor recurrence in 50–80% of patients at 5 years after treatment45.…”
mentioning
confidence: 99%